Teaching English Vocabulary Through Songs As Audio Aid At Sd Muhammadiyah 2 Banda Aceh - Sulicha, Rina; Handiana, Cut Mainy; Handayani, Linda (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The research aimed to ease elementary students to learn English vocabulary through lyrics of song. By using songs as audio media, the students at VI Class of SD Muhammadiyah 2 Banda Aceh City have capability to enlarge their English vocabularies.As a result, the students ease to communicate effectively and ease to learn tenses, grammar and able to master four basic skills in learning English (listening, speaking, reading and writing). The research used experimental design which is contained two classes that are the experimental class (VI-1) and the control class (VI-2). Pre-test and post-test is given for both classes (the experimental class and the cotrol class), but the treatment only gave in the experimental class (VI-1) that is using song as audio media in teaching English vocabulary. Meanwhile, in the control class (VI-2), the reseracher used visual aid such as picture card in teaching learning vocabulary. English vocabularies that taught for the students involved three topics that are Ordinal number, Names of fruits and Parts of human body. The sample of Classes of the research are selected by using random sampling which is contained VI-1 and VI-2 class. Both of classes consisted of 25 students. Data is analysed by using T-test form.